PENGARUH KOMBINASI DEKOKTA RIMPANG JAHE MERAH (Zingiber officinale var rubrum) DAN RIMPANG ALANG-ALANG (Imperata cylindrica) TERHADAP KADAR NITRAT SERUM DAN NITRAT JARINGAN SINOVIAL TIKUS YANG DIINDUKSI COMPLETE FREUND’S ADJUVANT - Mayvita Muntadiroh (Jurnal Kedokteran Komunitas, 2019)
Introduction: Osteoarthritis (OA) is a chronic degenerative disease associated with inflammatory processes and free radical formation. It causes damage to the joint cartilage progressively. The rhizome of red ginger and cogon grass (RRGC) have anti-inflammatory and antioxidant properties. The present study reported the potency of the herbals combination to reduce serum and synovial nitric oxide (NO) in OA rats. Nitrate (a stable form of NO) are measured in serum and synovial tissue of rats.Method: Male Wistar rats aged 4 months divided into 5 groups, namely; positive group, negative group, treatment 1 (doses 9 + 40 mg/day), treatment 2 (doses 18 + 40 mg/day) and treatment 3 (doses 36 + 40 mg/day). Rats were induced with 0.1 ml Complete Freund's Adjuvant (CFA) in intraarticular (IA) of the right knees. The decoction of RRGC combination was given at day 10 post induction (after edema was measured) for 10 days. Synovial and serum nitrate were examined using Nitric Oxide Colorimetric Assay Kit. Serum nitrate data were analyzed by Kruskal-Wallis continued with Mann-Whitney and synovial nitrate data using One Way ANOVA continued with Post Hoc. Result were considered to be significant if p<0,05.Results: The decoction of RRGC combination in treatment 1 (4,29±0,55) and treatment 3 (3,64±0,70) decrease serum nitrate levels of OA rats (p<0,05). The decoction of RRGC combination in treatment 1 (2,99±1,18), treatment 2 (2,87±0,41) dan treatment 3 (2,79±1,09) decrease synovial tissue nitrate levels of OA rats (p<0,05).Conclusion: The given doses reduce nitrat levels of synovial tissue (p<0,05). The herbals combination at dose 1 and 3 reduce both nitrat serum and synovial level. The combination of decoction of red ginger and cogon grass rhizome may have potential to be developed as anti-osteoarthritis agent.Keywords: Osteoarthritis, Red Ginger rhizome, Cogon Grass rhizome, Nitric Oxide, Nitrate